The application of waste marble as coarse aggregate in concrete production / Kok Yung Chang, Wai Hoe Kwan and Hui Bun Kua - Kok, Yung Chang; Wai Hoe Kwan, Hoe Kwan; Hui Bun Kua, Bun Kua (Institute of Research Management and Innovation (IRMI), 2018)
The massive growth of construction industry especially in the developing countries results in extensive quarrying activities which ultimately would lead to the depletion of natural resources. Apart from extensive extraction of the natural granite from the earth for concrete production, marble production industry is also majorly contributing to the quarrying activities. In addition, high volume of waste is generated by the marble production industry as 70% of marble is wasted during the production such as quarrying, cutting, processing and others which is environmental unfriendly. In a way to achieve sustainable construction, the present study is to utilise the waste marble in replacing the coarse aggregate in concrete production. The engineering performance including workability, compressive strength, ultrasonic pulse velocity (UPV) and chloride penetration were analysed. The raw waste marble obtained from the industry were crushed and sieved into maximum size 20 mm and used to replace the coarse aggregate at the level of 20%, 40%, 60%, 80% and 100% respectively. Results show that 60% of the replacement level has yield to optimum result by achieving the highest compressive strength and UPV at approximate 5% higher than the control. Meanwhile, the effect on chloride penetration resistance is more significant, i.e. approximate 19% better than the control. However, increasing the replacement level of waste marble has no significant effect on workability, although an increasing trend was observed.